2022
DOI: 10.22219/jrak.v12i3.22363
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Pencegahan Kecurangan Dalam Alokasi Dana Desa

Abstract: The purpose of this study is to find empirical evidence regarding the effect of competence, morality, integrity, internal control and organizational culture on the fraud prevention in allocation of village funds. The sample in this study are obtained from 148 respondents from village officials in Denpasar. Multiple regression analysis is used to answer the hypothesis in this study. The results of the study find that competence, morality, internal control and organizational culture has a positive effect on frau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
0
0
1
Order By: Relevance
“…Therefore, it can be concluded that the relationship between the violation reporting system and fraud prevention in the Gorontalo-Indonesia Provincial Government is both positive and significant. In line with another research by Satcitanandadewi & Wahyuni (2020), it is also stated that internal control has a significant impact on fraud prevention. H3 : Whistleblowing Systems influences fraud prevention management of grant funds from Bawaslu Jambi Province and Bawaslu Districts/Cities throughout Jambi Province.…”
Section: Whistleblowing Systems For Fraud Preventionsupporting
confidence: 75%
“…Therefore, it can be concluded that the relationship between the violation reporting system and fraud prevention in the Gorontalo-Indonesia Provincial Government is both positive and significant. In line with another research by Satcitanandadewi & Wahyuni (2020), it is also stated that internal control has a significant impact on fraud prevention. H3 : Whistleblowing Systems influences fraud prevention management of grant funds from Bawaslu Jambi Province and Bawaslu Districts/Cities throughout Jambi Province.…”
Section: Whistleblowing Systems For Fraud Preventionsupporting
confidence: 75%
“…seperti sikap, kepribadian, karakter, dan kemampuan, sedangkan faktor eksternal adalah penyebab perilaku yang berasal dari luar diri individu seperti lingkungan dan kondisi tertentu. Perilaku kecurangan terjadi karena dipengaruhi oleh faktor internal dan eksternal (Susandya et al, 2022). Teori atribusi memiliki relevansi dengan penelitian ini.…”
Section: Jaa 64unclassified